2007
DOI: 10.1080/00016480600951517
|View full text |Cite
|
Sign up to set email alerts
|

Survival study and treatment strategy for second primary malignancies in patients with head and neck squamous cell carcinoma and nasopharyngeal carcinoma

Abstract: The survival rate of patients with SPMs is not significantly poor. The survival is worse if the SPM is associated with a primary advanced stage index cancer or it is synchronous; if the SPM occurs in an area other than the head and neck region; or if SPM patients undergo palliative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 11 publications
6
35
1
Order By: Relevance
“…There have been several studies that examined the prognoses of patients with SPMs (Rafferty and O'Dwyer 2001;Di Martino et al 2002;Tsou et al 2007;Rennemo et al 2008;Chen et al 2010;Dequanter et al 2011). Those studies reported that the prognoses of patients with synchronous SPMs are significantly lower than those with metachronous SPMs and that SPMs in the esophagus or lung contribute to the poorer outcome than the other types of SPMs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies that examined the prognoses of patients with SPMs (Rafferty and O'Dwyer 2001;Di Martino et al 2002;Tsou et al 2007;Rennemo et al 2008;Chen et al 2010;Dequanter et al 2011). Those studies reported that the prognoses of patients with synchronous SPMs are significantly lower than those with metachronous SPMs and that SPMs in the esophagus or lung contribute to the poorer outcome than the other types of SPMs.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence from recent investigations into UAD-SPT confirms that patients afflicted with HNSCC-SPT fare better than those with SPT of other origins (pulmonary or oesophageal) [3][4][5][6]. Most recently we analysed the effects of radiotherapy in larynngeal SCCs.…”
Section: Discussionmentioning
confidence: 98%
“…Studies differ widely (2-30%) in their estimated risk of SPT development in part due to inconsistencies in patient selection or diagnostic criteria as well as generally inadequate follow up ( [3][4][5][6]8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is generally accepted that diagnosis of the index tumour in concert with the premise of field cancerisation imparts a subsequent permanent risk of developing SPT [2][3][4][5][6]20,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tsou et al, 22 in managing SPT in patients with head and neck SCC, curative rather than palliative treatment is preferred when the index tumors have been diagnosed early, when SPT are metachronous and occurs in the head and neck region and also in cases of patients younger than 70 years. The chosen treatment for our patient was curative ranging from surgical resection with and without RT/chemotherapy.…”
Section: Discussionmentioning
confidence: 99%